Cyclic stretching-induced epithelial cell reorientation is driven by microtubule-modulated transverse extension during the relaxation phase - Jui-Chien Lien (Nature Portfolio, 2021)
Abstract Many types of adherent cells are known to reorient upon uniaxial cyclic stretching perpendicularly to the direction of stretching to facilitate such important events as wound healing, angiogenesis, and morphogenesis. While this phenomenon has been documented for decades, the underlying mechanism remains poorly understood. Using an on-stage stretching device that allowed programmable stretching with synchronized imaging, we found that the reorientation of NRK epithelial cells took place primarily during the relaxation phase when cells underwent rapid global retraction followed by extension transverse to the direction of stretching. Inhibition of myosin II caused cells to orient along the direction of stretching, whereas disassembly of microtubules enhanced transverse reorientation. Our results indicate distinct roles of stretching and relaxation in cell reorientation and implicate a role of myosin II-dependent contraction via a microtubule-modulated mechanism. The importance of relaxation phase also explains the difference between the responses to cyclic and static stretching.